Macrolide Therapy in Respiratory Viral Infections - Jin-Young Min; Yong Ju Jang (Mediators of Inflammation)
Background. Macrolides have received considerable attention for their anti-inflammatory and immunomodulatory actions beyond the antibacterial effect. These two properties may ensure some efficacy in a wide spectrum of respiratory viral infections. We aimed to summarize the properties of macrolides and their efficacy in a range of respiratory viral infection. Methods. A search of electronic journal articles through PubMed was performed using combinations of the following keywords including macrolides and respiratory viral infection. Results. Both in vitro and in vivo studies have provided evidence of their efficacy in respiratory viral infections including rhinovirus (RV), respiratory syncytial virus (RSV), and influenza virus. Much data showed that macrolides reduced viral titers of RV ICAM-1, which is the receptor for RV, and RV infection-induced cytokines including IL-1β, IL-6, IL-8, and TNF-α. Macrolides also reduced the release of proinflammatory cytokines which were induced by RSV infection, viral titers, RNA of RSV replication, and the susceptibility to RSV infection partly through the reduced expression of activated RhoA which is an RSV receptor. Similar effects of macrolides on the influenza virus infection and augmentation of the IL-12 by macrolides which is essential in reducing virus yield were revealed. Conclusion. This paper provides an overview on the properties of macrolides and their efficacy in various respiratory diseases.